Development of Open Source GIS Based Field Service Management software for Pharmaceutical Industries - Patel, Jinal J; Shukla, Shital; Gaikwad, Santosh (International Journal of Computer Sciences and Engineering, 2020)
Managing human resources in today’s dynamic environment is an essential function as well as important. Pharmaceutical Companies have medical representatives to present their product in the market. The growth of these pharmaceutical companies is depending on the presentation of the product by medical representative to the doctor/ Clinics. In a previous time, most of these companies managed their employee’s information through paper processing. Paper based processing has several limitations hence a Field Service Management Software (FSMS) has been developed for digital information recording and processing. Through this FSMS, a Manager can store, manage and track employee’s information in near real time. This paper presents a FSMS on West part of Ahmadabad, Gujarat which was developed using free and open source software (FOSS4G). This system has a study related data like hospital, clinic, and Pharmaceutical company location, roads in the study area and ward boundary. In this system, a manager can get the live information about all employees on their screen using GPS system. Furthermore, the manager can also store and manage all details of the employees. This application considerably reduces paperwork and save one's precious time apart from being very convenient.